Interfaith just peacemaking: Jewish, Christian, and Muslim perspectives on the new paradigm of peace and war - Thistlethwaite, Susan Brooks (Palgrave Macmillan, 2012)
Interfaith Just Peacemaking is a collected work by 27 Jewish, Muslim and Christian scholars and religious leaders on the ten 'practice norms' of the peacemaking paradigm called 'Just Peace.'Just Peace theory, like the paradigm it most resembles, Just War theory, is a list of specific practices that are applied to concrete contexts